Răspuns:
Explicație pas cu pas:
a) a₁ = -1 ; r = 3 ; n = 12 ; S₁₂ = ?
aₙ = a₁ + (n-1)·r
a₂ = a₁+r = -1+3 = 2
a₁₂ = -1 + 11·3 = -1+33 = 32
S₁₂ = a₁+a₂+...+a₁₂ = -1+2+5+...+32 = (-1+32)·12:2 = 31·6 = 186
b) a₁ = 100 ; r = 2 ; n = 60 ; S₆₀ = ?
a₂ = a₁+r = 100+2 = 102
a₆₀ = 100 + 59·2 = 100+118 = 218
S₆₀ = 100+102+104+...+218 = (100+218)·60:2 = 318·30 = 9540
c) a₇ = 17 ; a₂ = 2 ; n = 50 ; S₅₀ = ?
a₂ = a₁+r ; a₇ = a₁+6r => a₇-a₂ = 5r = 17-2 = 15 => r = 15:5 => r = 3
a₁ = 2-3 = -1 ; a₅₀ = a₁+49r = -1+49·3 = 146
S₅₀ = -1+2+....+146 = (-1+146)·50:2 = 145·25 = 3625
d) a₃ = -12 ; a₅ = 36 ; n = 20 ; S₂₀ = ?
a₅ = a₁+4·r ; a₃ = a₁+2·r => a₅-a₃ = 2r = 36-(-12) = 48 => r = 48:2
r = 24 ; a₁ = a₃-2·r = -12-48 = -60
a₂₀ = a₁+19·r = -60 + 19·24 = 396
S₂₀ = -60-36-12+12+.....+396
S₂₀ = (-60+396)·20:2 = 336·10 = 3360